Pylorus-preserving pancreaticoduodenectomy (pp Whipple) versus pancreaticoduodenectomy (classic Whipple) for surgical treatment of periampullary and pancreatic carcinoma - Diener, Markus K (Cochrane Database Syst Rev, 2014)
BACKGROUND: Pancreatic cancer is the fourth leading cause of cancer death for men and the fifth for women. The standard treatment for resectable tumours consists of a classic Whipple (CW) operation or a pylorus-preserving pancreaticoduodenectomy (PPW). It is unclear which of these procedures is more favourable in terms of survival, mortality, complications and quality of life. OBJECTIVES: The objective of this systematic review is to compare the effectiveness of CW and PPW techniques for surgical treatment of cancer of the pancreatic head and the periampullary region. SEARCH METHODS: We conducted searches on 28 March 2006, 11 January 2011 and 9 January 2014 to identify all randomised controlled trials (RCTs), while applying no language restrictions. We searched the following electronic databases: the Cochrane Central Register of Controlled Trials (CENTRAL), the Cochrane Database of Systematic Reviews (CDSR) and the Database of Abstracts of Reviews of Effects (DARE) from The Cochrane Library (2013, Issue 4); MEDLINE (1946 to January 2014); and EMBASE (1980 to January 2014). We also searched abstracts from Digestive Disease Week and United European Gastroenterology Week (1995 to 2010). We identified no additional studies upon updating the systematic review in 2014. SELECTION CRITERIA: We considered RCTs comparing CW versus PPW to be eligible if they included study participants with periampullary or pancreatic carcinoma. DATA COLLECTION AND ANALYSIS: Two review authors independently extracted data from the included studies. We used a random-effects model for pooling data. We compared binary outcomes using odds ratios (ORs), pooled continuous outcomes using mean differences (MDs) and used hazard ratios (HRs) for meta-analysis of survival. Two review authors independently evaluated the methodological quality and risk of bias of included studies according to the standards of The Cochrane Collaboration. MAIN RESULTS: We included six RCTs with a total of 465 participants. Our critical appraisal revealed vast heterogeneity with respect to methodological quality and outcome parameters. In-hospital mortality (OR 0.49, 95% confidence interval (CI) 0.17 to 1.40; P value 0.18), overall survival (HR 0.84, 95% CI 0.61 to 1.16; P value 0.29) and morbidity showed no significant differences. However, we noted that operating time (MD -68.26 minutes, 95% CI -105.70 to -30.83; P value 0.0004) and intraoperative blood loss (MD -0.76 mL, 95% CI -0.96 to -0.56; P value < 0.00001) were significantly reduced in the PPW group. All significant results are associated with low quality of evidence as determined on the basis of GRADE (Grades of Recommendation, Assessment, Development and Evaluation) criteria. AUTHORS’ CONCLUSIONS: No evidence suggests relevant differences in mortality, morbidity and survival between the two operations. Given obvious clinical and methodological heterogeneity, future research must be undertaken to perform high-quality randomised controlled trials of complex surgical interventions on the basis of well-defined outcome parameters.